United Nations Commission on International Trade Law (UNCITRAL) Yearbook 2004 - Nations Unies (United Nations, 2008)
The Yearbook covers the Commission’s work on its annual session as well as related documents, studies, reports and notes. This thirty-fifth volume consists of three parts. Part one contains the Commission’s report on the work of its 37th session (2004), and the action thereon by the United Nations Conference on Trade and Development (UNCTAD) and by the General Assembly. Part two includes reports of the Commission’s Working Groups as well as studies, reports and notes by the Secretary-General and the Secretariat, and selected working papers that were prepared for the Working Groups. Part three contains the Legislative Guide on Insolvency Law, Explanatory Note on the United Nations Convention on the Assignment of Receivables in International Trade, and bibliography of recent writings related to the Commission’s work.